NILAI ESTETIS BATIK GARUT PEGUNUNGAN DAN PESISIR - Ira Adriati (Jurnal Budaya Nusantara, 2019)
Batik is a result of a tradition of ownership owned by various regions in Indonesia. One ofthe areas in West Java is known as Batik Priangan, including the region of Garut. Each regionin Priangan has a batik that is batik with unique motifs and coloring in each region. In this paper,it describes the aesthetic value of batik Garut in the mountainous areas with the coastal areas.This research uses historical approach, the value of tradition-oriented, and in cultural acculturation.Based on the analysis, it can be known that the waters can be different from the visualizationof batik motifs in the mountainous regions, which tend to be classic motifs, typical of the latenight and the coast of the region. The other difference appears from the ability of the craftsmen,the craftsmen in the mountainous regions show more detailed and smooth skills, while on thecoast there is no detail.